Pengaruh literasi keuangan, financial technology, dan dompet online pada kinerja keuanggan UMKM: peran moderasi inklusi keuangan (studi kasus UMKM di Kota Yogyakarta) - Sri Ayem; Umi Wahidah; Dyah Ari Susanti; Supatman Supatman; Nila Sinta Yovita; Suddin Lada (Universitas Widya Mataram, 2025)
This study analyzes the effect of financial literacy, financial technology, and e-wallets on the financial performance of MSMEs, with financial inclusion as a moderating variable among MSMEs in Yogyakarta City. Using a quantitative method with 100 MSME respondents selected through purposive sampling, the multiple linear regression results show that financial literacy and financial technology positively influence financial performance, while e-wallets have no significant effect. The Moderated Regression Analysis (MRA) indicates that financial inclusion does not moderate the relationship between the three independent variables and MSME financial performance. Simultaneously, all three variables affect financial performance. Theoretically, this study expands the application of RBV and TAM by integrating knowledge and digital technology aspects, enriching the literature on MSME performance determinants in the Industry 4.0 era. Practically, the findings provide insights for MSMEs, policymakers, and financial institutions to enhance financial literacy and the adoption of financial technologies.